Is there a crisis in international environmental and development policy? After the Johannesburg summit - Andreas Rechkemmer (Stiftung Wissenschaft und Politik (SWP), 2002)
Some two months after the UN Summit on Sustainable Development in Johannesburg discussion is now focused on how to effectively implement the resolutions that were passed on such matters as fighting poverty, protecting natural resources and changing modes of production and consumption. For many observers and decision makers, the least-common-denominator-type consensus that was reached - typical for UN-brokered compromises - does not go far enough. They are asking whether alternative approaches for the implementation of international agreements is possible. The German-European unilateral course on renewable energy suggests a pragmatic and promising development for making progress in environmental and development policy, despite the current paralysis of multilateral mechanisms in international politics.(SWP Comments / SWP)
Keywords: 320